2018
DOI: 10.1109/twc.2018.2849413
|View full text |Cite
|
Sign up to set email alerts
|

Uplink Non-Orthogonal Multiple Access With Finite-Alphabet Inputs

Abstract: This paper focuses on the non-orthogonal multiple access (NOMA) design for a classical two-user multiple access channel (MAC) with finite-alphabet inputs. In contrast to most of existing NOMA designs using continuous Gaussian input distributions, we consider practical quadrature amplitude modulation (QAM) constellations at both transmitters, the sizes of which are assumed to be not necessarily identical.We propose to maximize the minimum Euclidean distance of the received sum-constellation with a maximum likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In this section, we aim to solve Problem 2 to find the differential pairs (m, n) having the minimum Euclidean distance. For this purpose, we first introduce the definition of the punched Farey sequence developed in [9].…”
Section: B the Minimum Euclidean Distance Of The Constellation Pointmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we aim to solve Problem 2 to find the differential pairs (m, n) having the minimum Euclidean distance. For this purpose, we first introduce the definition of the punched Farey sequence developed in [9].…”
Section: B the Minimum Euclidean Distance Of The Constellation Pointmentioning
confidence: 99%
“…The formulated problem is a mixed continuousdiscrete problem that is in general non-trivial to resolve. To tackle it, we resort to the punched Farey sequence framework developed in [9] to strategically segment the entire feasible region of the formulated optimization problem into a finite number of sub-intervals and obtain the closed-form optimal solution of the formulated problem in each sub-interval. We then acquire the optimal solution to the formulated problem by comparing the solutions on each sub-interval.…”
Section: Introductionmentioning
confidence: 99%
“…This system model can be seen as the equivalent model of many common scenarios, such as the one-cell system with two users [22] or two-cell system with the user located in the two cells' overlapping area [23]. We consider that the transmitted signals are drawn from unipolar pulse amplitude modulation constellations, motivated by the fact that 1) the transmitted signals in realistic communication systems are drawn from finite-alphabet constellations [19], [24], [25] 2) the transmitted signals in VLC systems must be nonnegative and real-valued. We assume that the i -th (i = 1, 2) user transmits K i bit data to the PD receiver over L successive channels.…”
Section: System Modelmentioning
confidence: 99%
“…It is shown that the relative rotation of the constellation on one user enhances the achievable rate region. This result has been extended to several other channel models including multiple‐input multiple‐output (MIMO) channel, non‐orthogonal multiple access (NOMA) [4], and NOMA with a rotation of constellation [5]. A finite constellation over a fast fading wiretap channel is studied in [6] and further finite constellations over an AWGN wiretap channel is also reported in [7].…”
Section: Introductionmentioning
confidence: 99%